UV filters induce transcriptional changes of different hormonal receptors in Chironomus riparius embryos and larvae. (July 2016) - Ozáez, Irene; Aquilino, Mónica; Morcillo, Gloria; Martínez-Guitarte, José-Luis
Abstract: Organic ultraviolet (UV) filters are emerging contaminants that are ubiquitous in fresh and marine aquatic systems due to their extensive use in cosmetics, plastics, paints, textiles, and many other industrial products. The estrogenic effects of organic UV filters have been long demonstrated in vertebrates, and other hormonal activities may be altered, according to more recent reports. The impact of UV filters on the endocrine system of invertebrates is largely unknown. We have previously reported that some UV filters may affect ecdysone-related genes in the aquatic insect Chironomus riparius, an ecotoxicologically important model organism. To further analyze other possible effects on endocrine pathways, we first characterized four pivotal genes related with hormonal pathways in insects; thereafter, these genes were assessed for alterations in transcriptional activity after exposure to 4-methylbenzylidene camphor (4MBC) or benzophenone-3 (BP-3), two extensively used sunscreens. We found that both chemicals disturbed the expression of all four genes analyzed: hormonal receptor 38 ( HR38 ), methoprene-tolerant ( Met ), membrane-associate progesterone receptor ( MAPR ) and insulin-like receptor ( INSR ), measured by changes in mRNA levels by real-time PCR. An upregulatory effect at the genomic level was detected in different developmental stages. Interestingly, embryos appeared to be more sensitive to the action of the UV filters than larvae. Our results suggest that the risk of disruption through different endocrine routes is not negligible, considering the significant effects of UV filters on key hormonal receptor and regulatory genes. Further effort is needed to develop environmental risk assessment studies on these pollutants, particularly for aquatic invertebrate model organisms. Highlights: Four hormonal receptors have been identified in the diptera Chironomus riparius . 4MBC upregulates HR38 and Met in embryos but only Met in larvae. BP-3 upregulates HR38, Met, MAPR, and INSR in embryos but only INSR in larvae. Embryos are more sensitive than larvae to these two UV filters. UV filters could alter several endocrine routes simultaneously in invertebrates. Abstract : The UV filters 4MBC and BP-3 upregulate the transcription of four hormonal receptors related to different endocrine routes in Chironomus riparius larvae and embryos.